2019
DOI: 10.1186/s12870-019-2173-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profile comparison of a graft chimera ‘Hongrou Huyou’ (Citrus changshan-huyou + Citrus unshiu) and its two donor plants

Abstract: BackgroundChimeras synthesized artificially by grafting are crucial to the breeding of perennial woody plants. ‘Hongrou Huyou’ (Citrus changshan-huyou + Citrus unshiu) is a new graft chimera originating from the junction where a Citrus changshan-huyou (“C”) scion was top-grafted onto a stock Satsuma mandarin ‘Owari’ (C. unshiu, “O”). The chimera was named OCC because the cell layer constitutions were O for Layer 1(L1) and C for L2 and L3. In this study, profiles of primary metabolites, volatiles and carotenoid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Nootkatone (14) is one of the characteristic aroma components in the peel of CACH. Zhang et al (2019) analyzed the volatile components and carotenoids in the peel and juice of CACH. They identified 36 compounds including monoterpenes and sesquiterpenes, such as β-Myrcene (15), γ-elemene, Sabinene (24) and α-terpinene (27),etc., At the same time, they found phytoene of eight carotenoids was detected only in juice.…”
Section: Chemical Constituentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nootkatone (14) is one of the characteristic aroma components in the peel of CACH. Zhang et al (2019) analyzed the volatile components and carotenoids in the peel and juice of CACH. They identified 36 compounds including monoterpenes and sesquiterpenes, such as β-Myrcene (15), γ-elemene, Sabinene (24) and α-terpinene (27),etc., At the same time, they found phytoene of eight carotenoids was detected only in juice.…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…In addition to the above components, there are various known complex components in CACH, such as organic acids ( Lu et al, 2018 ) (No. 64–86, Table 1 ), amino acids ( Zheng et al, 2016 ), sugars ( Zhang et al, 2019 ), and inorganic elements (101) ( Xu et al, 2008 ). Some studies have been reported on the content and types of them.…”
Section: Chemical Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, the characters occurring in composite plants were somewhat different from both the rootstock and scion, which was likely due to a combination or as a result of physiological interactions between scion and the rootstock (Killiny et al 2016;Tietel et al 2020). A study of metabolites comparisons on Citrus grafts conducted by Zhang et al (2019) revealed that the characters of chimeras synthesized artificially by grafting could be dominant in one plant donor, but in other characters, it was closer to other donors. In the case where the metabolite profile of the Tawangmangu autograft was not more similar to Tawangmangu, the most probable cause is that the grafting process might induce a stress response in plants.…”
Section: A B C Dmentioning
confidence: 99%